Combination of body mass index and body fat percentage in middle and late pregnancy to predict pregnancy outcomes in patients with gestational diabetes in Wenzhou, China: a single-centre retrospective cohort study - Tao You; Zhi Zheng; Yilin Chen; Bingru Chen; Lanxi Chen; Xiner Zhao; Shuoru Zhu (BMJ Open)
Objectives The present study aimed to evaluate whether body mass index (BMI) and body fat percentage (BFP) could be used to predict pregnancy outcomes in patients with gestational diabetes mellitus (GDM).Design Retrospective cohort study.Setting Wenzhou Medical University Affiliated Second Hospital (Zhejiang Province, China). Clinical data were collected from electronic medical records.Participants Data from 683 patients with GDM admitted to the Wenzhou Medical University Affiliated Second Hospital between January 2019 and December 2021 were retrospectively analysed.Outcome measures Pregnancy outcomes.Results The results showed that pregnant women with BFP ≥33% were more prone to abnormal amniotic fluid volume, abnormal blood pressure and anaemia (p<0.05). Additionally, these patients were more likely to experience postpartum haemorrhage and macrosomia, as well as risk factors associated with caesarean section at labour (p<0.05). BMI exhibited a strong predictive value for abnormal blood pressure (OR 1.170; 95% CI 1.090 to 1.275), anaemia (OR 1.073; 95% CI 1.016 to 1.134), caesarean section (OR 1.150; 95% CI 1.096 to 1.208) and macrosomia (OR 1.169; 95% CI 1.063 to 1.285). Additionally, classified BFP had a predictive value for abnormal amniotic fluid volume (OR 3.196; 95% CI 1.294 to 7.894), abnormal blood pressure (OR 2.321; 95% CI 1.186 to 4.545), anaemia (OR 1.817; 95% CI 1.216 to 2.714), and caesarean section (OR 1.734; 95% CI 1.270 to 2.367).Conclusions The results suggest that patients with GDM with BFP ≥33% were more likely to experience unfavourable pregnancy outcomes, undergo caesarean section and develop macrosomia. The combination of BMI with classified BFP could better predict abnormal blood pressure and caesarean section in patients with GDM during the middle and late stages of pregnancy.